Renewable energy certificates and electricity trading models: Bi-level game approach. (September 2021) - Tao, Yuechuan; Qiu, Jing; Lai, Shuying; Zhao, Junhua
Highlights: A pricing model for renewable energy certificates is proposed. The combination of the REC market and ETS can promote emission reduction. The cooperation of renewable energy plants and P2GSes increases the profit of collision. Abstract: To reduce carbon emissions in the power sector, the emissions trading system (ETS) is widely used to mitigate emissions from thermal generators. Also, large-scale and distributed renewable energy is invested to replace conventional thermal generators. Renewable energy certificates (RECs) are designed to support the prior dispatch of renewable energy. However, the purchase motivation for RECs is worth attention. In this paper, a theoretical methodology is proposed to promote transactions of RECs. The cooperation of renewable power plants and the emerging storage technology, e.g., power-to-gas (P2G), is considered to further reduce emissions. In the proposed bi-level model, which is based on the game approach, the thermal generators can purchase RECs and convert them to carbon emission quotas. The oligopoly market is considered to reveal the real payoffs of thermal generators, renewable power plants, and power-to-gas stations (P2GSes). The proposed model is verified on the IEEE 30-bus system. It is found that the RECs can help renewable energy plants increase income by 19.4% without considering cooperation, and more renewable energy is dispatched as priority. It can be concluded that the cooperation of P2GSes and renewable plants considering the RECs can increase the collision payoffs and smooth the output of renewable energy. Sensitive analysis reveals the interaction between the carbon market and the RECs market.